Prawo karne wobec narkomanii (uwagi na tle ustawy z dnia 31 I 1985 r.) - Gaberle, Andrzej; Ostrowska, Mariola (Wydział Prawa i Administracji UAM, 1985)
As one observes the development of penal law, one has to arrive at the conclusion that it is undergoing an evolution in the direction of. lightening the measures employed, although this development often meets difficulties. Also, what is becoming increasingly marked is the need to bind penal measures more closely with the non-judical systems of social control, as penal sanctions alone often prove to be ineffective. Hence the growing emphasis in international conventions devoted to drug habit prevention, on substituting penal measures with other measures of influence; many countries have taken such postulates into account in their legal regulations of the drug addiction problem. The problem is not easy to solve, though. Criminal acts connected with drug addiction consist not only of the taking and production of drugs, the drug traffic etc, but also of „ordinary" criminal acts being commited, such as, for e.g. burglaries, forgeries, thefts. In addition, many addicts show symptoms of a social alienation still prior to the beginning of the addicition, as, among others, a criminal past. The application of medical measures in such cases is made all the more difficult, and makes on turn to penal sanctions, first of all to decisions of confinement, which dominate the picture of drug addict convictions. The Prevention of the Drug Habit Act does not contain any solutions which could bring anything new into the present situation. The penal law solutions provided for are "traditional"; they do not create any possibility to omit the prosecution of the addict willing to undergo medical treatment, which does not open positive perspectives on freeing him or her of the addiction. It also to often employs the confinement penalty, turning it into the most important means of combating criminal acts connected with the habit. Thus, the Act selects a "conservative" option from all the different possible options of penal law regulation of the problem, and does not constitute any step forward in the direction of creating a modern penal law system.
Penal Law on Drug Addiction. Remarks on the Prevention of the Drug Habit Act of 31 Jan. 1985